2022
DOI: 10.1093/braincomms/fcac288
|View full text |Cite
|
Sign up to set email alerts
|

Ependymal cells and neurodegenerative disease: outcomes of compromised ependymal barrier function

Abstract: Within the CNS, ependymal cells form critical components of the blood-CSF barrier and the CSF-brain barrier. These barriers provide biochemical, immunological, and physical protection against the entry of molecules and foreign substances into the CSF while also regulating CSF dynamics, such as the composition, flow, and removal of waste from the CSF. Previous research has demonstrated that several neurodegenerative diseases, such as Alzheimer’s disease and multiple sclerosis, display irregularities in ependyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 133 publications
(177 reference statements)
3
7
0
Order By: Relevance
“…Interactions within ependymal cells and oligodendrocytes were shown to decrease significantly with age, while interactions within astrocytes and from astrocytes to neurons significantly increased with age. This reflects the current understanding that the ependymal layer thins during aging and reactive astrocytes proliferate and interpose themselves within the ependymal cell layer [25, 26]. Oligodendrocyte numbers and function are also known to decrease with age while astrocyte interactions increase, which is shown in our findings [27, 28, 29].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Interactions within ependymal cells and oligodendrocytes were shown to decrease significantly with age, while interactions within astrocytes and from astrocytes to neurons significantly increased with age. This reflects the current understanding that the ependymal layer thins during aging and reactive astrocytes proliferate and interpose themselves within the ependymal cell layer [25, 26]. Oligodendrocyte numbers and function are also known to decrease with age while astrocyte interactions increase, which is shown in our findings [27, 28, 29].…”
Section: Resultssupporting
confidence: 88%
“…In the aging brain, astrocytes were shown to become more active, not only increasing their interaction strength but also the types of LR interactions, which is consistent with the current understanding of the roles of astrocytes in aging [27,28,29,30,31,32,33,34,35]. The thinning of the ependymal layer expected in aging was also shown by the observed decrease in ependymal interactions in aging [25,26].…”
Section: Discussionsupporting
confidence: 81%
“…Ependymal cells are essential for neuronal development. 61 It is reported that hydrocephalus can be caused by mutations in MPDZ gene that leads to ependymal malformation, 62 and by deletion of SNX27 or YAP that impairs ependymal cell differentiation. 37 , 63 Importantly, in mutant hydrocephalus with hop gait (hyh) mice, 64 ependymal denudation develops before the onset of hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“… 100 Deregulated ependyma can impair these process during brain development leading to increased risk for neurodegenerative diseases. 101 Cav1 is known to influence cell proliferation and death 11 , 24 , 102 by controlling specific apoptosis genes. 103 , 104 Cav1 is regarded as a master regulator of cellular senescence.…”
Section: Discussionmentioning
confidence: 99%